The Improvement of School Principal Performance of SMP Sampang through Managerial Supervision - Solikin Solikin (Faculty of Education Universitas Negeri Malang, 2020)
Purposed of the research is to improve Principal performance using managerial supervision. The research was conducted in three schools in Sampang. This research using school action research with two cycle, result of the research it found in cycle I that 81 percent of teachers understand about class supervision, but they could not implement it based on the characteristics. In cycle, there is an increase of understanding from (cycle I) on average reaches score 29,90 percent to 45,47 percent. Cycle III there is an increase in supervision competence, from the average (cycle II) reaches score of 45.47 percent to 50.42 percent.